2021
DOI: 10.3389/fmed.2020.608903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Collagen Tripeptide and Adjusting for Climate Change on Skin Hydration in Middle-Aged Women: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Introduction: Although collagen is widely used in various forms as a functional ingredient in skin care products, the effect of oral supplementation of collagen tripeptides (CTPs) on human skin is unclear. Moreover, the majority of the positive outcomes of CTP reported so far have not considered the effect of weather conditions. Therefore, we tested the effect of CTP and adjusting for climate change on skin properties in middle-aged women.Materials and Methods: A randomized controlled trial was conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 44 publications
0
28
0
1
Order By: Relevance
“…In animal experiments, the expression of HSP27 was increased in the tissues with UVB exposure, and siRNA was also applied to specifically down-regulate the expression of HSP27 in mice ear skin ( Figures 4A,B ). Studies illustrated that epidermal incrassation and differentiation in connective tissue were prevalent in photodamage skin ( Tak et al, 2020 ). H&E and Masson-trichrome staining were used to assess the histopathologic changes of mice skin after 24 h of the last UVB irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…In animal experiments, the expression of HSP27 was increased in the tissues with UVB exposure, and siRNA was also applied to specifically down-regulate the expression of HSP27 in mice ear skin ( Figures 4A,B ). Studies illustrated that epidermal incrassation and differentiation in connective tissue were prevalent in photodamage skin ( Tak et al, 2020 ). H&E and Masson-trichrome staining were used to assess the histopathologic changes of mice skin after 24 h of the last UVB irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Although the antioxidant ability of the CTP is due to the presence of hydrophobic amino acids in the peptide [10], the exact molecular mechanism underlying how the CTP acts as an antiaging product has not been fully uncovered. A previous placebo-controlled clinical trial demonstrated that oral ingestion of the CTP helped retain skin water contents [11]. Moreover, a recent study on the cutaneous hydration effect of CTP intake in mice showed significant reductions in transepidermal water loss, scratching behavior, and levels of hyaluronidase-1, tumor necrosis factor-alpha, and interleukin-6, while showing increased water content and hyaluronan synthase-2 levels; these results suggested that CTP products could enhance skin hydration with potential as a skin hydration agent [12].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed the biological effects of CTP, including the acceleration of fracture healing [ 2 ], improving experimental osteoarthritis [ 5 ], exerting an anti-inflammatory effect for patients with atopic dermatitis [ 6 ] and antiphotoaging effects [ 7 ], and improving dry skin [ 8 , 9 ]. Previous studies have shown that CTP induces collagen expression via a p38 mitogen-activated protein kinase cascade [ 29 ] and inhibits dipeptidyl peptidase-4 activity [ 30 ], but the molecular mechanisms and signaling pathways underlying these biological effects have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Hakuta et al reported an anti-inflammatory effect of CTP for patients with atopic dermatitis and inhibitory effects of secretions of inflammatory cytokines and chemokines in vitro [ 6 ]. Additionally, oral administration of CTP improved skin barrier function in ultraviolet B-exposed hairless mice [ 7 ] and dryness or pruritus of dry skin in humans [ 8 , 9 ]. For atherosclerosis, an inhibitory effect of CTP on atherosclerosis development was shown in atherosclerosis model rabbits [ 10 ].…”
Section: Introductionmentioning
confidence: 99%